ANALISIS KINERJA KEUANGAN PEMERINTAH DESA PADA DESA SEI MERAH KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Pangaribuan, Jonner; Sirait, Josua (UNIKA Santo Thomas, 2023)
This study aimed to determine the financial performance of the village government in Sei Merah Village, Tanjung Morawa District, Deli Serdang Regency, in 2018-2022. The population in this study are the elements in the Village Revenue and Expenditure Budget Realization Report (APBDes) in Sei Merah Village, Tanjung Morawa District, Deli Serdang Regency. The sample in this study is a saturated sample using elements of the Village Revenue and Expenditure Budget Realization Report (APBDes) in Sei Merah Village for five years, namely 2018-2022. The analysis technique in this study is to use quantitative descriptive using financial ratios, namely the independence ratio, effectiveness and efficiency ratio, harmony ratio, and growth ratio. The results showed that the financial performance of the government of Sei Merah Village, Tanjung Morawa District, Deli Serdang Regency in 2018-2022 based on the independence ratio was categorized as very low, the effectiveness ratio was classified as very effective, the efficiency ratio was categorized as inefficient, the harmony ratio was still very much dominated by routine spending rather than development spending and the growth ratio is classified as medium growth. Overall, the financial performance of the Sei Merah village government in 2018-2022 is deficient. Although the village government has succeeded in realizing the village's original income very effectively and the growth of the village's original income is quite good, the Sei Merah village government is still very low in independence, the use of funds is inefficient, the allocation of routine expenditure is very high, and the development expenditure is low.